Investigating translation strategies used by students in translating metaphors from English into Indonesian: A case study on translation - Sinambela, Erika; Sipayung, Rohdearni Wati; Herman, Herman; Purba, Ridwin; Fatmawati, Endang; Ngongo, Magdalena; Manurung, Lastri Wahyuni (Research Journal in Advanced Humanities, 2024)
The main interest of this study is to analyze the translation strategies used by the students of the English Department in translating metaphors from English into Indonesian and how the students choose their translation strategies in translating the source text into the target text related to the metaphorical meanings. This study used a descriptive-qualitative research design by using linguistic data. The linguistic data is the translation results produced by the students at the English Department of Universitas HKBP Nommensen, Medan. The students are randomly chosen as the participants of the study. A questionnaire of metaphorical stimuli and an interview are adapted to collect the data. The results showed that metaphorization strategy was the most effective strategy used by the students in translating metaphor from English into Indonesian. Based on the data analysis conducted, overall there is a minor difference in the use of translation strategies by students. In the case of metaphor variation, students often change metaphors of the form of the verb, noun, or adjective into the form of the verb, noun, or adjective, but not vice versa.